Assessment of the Numeracy Tutorial Service of Project KaISIPnayan: Inputs to the Sustainable Extension Program - Flordeliza B Ferrer; Jojo I Baltazar; Gina Fe S Legaspi; Czarina Paulyn O Borja; Reinalyn P Briones; Bai Hasmin A Canapia; Gracezel Ann E Garita; Angelica Mae Yacap (Journal of Elementary and Secondary School, 2024)
This study provides an overview of an assessment conducted on the numeracy tutorial service, namely Project KaISIPnayan. This study aims to evaluate the effectiveness and sustainability of the program, with the objective of enhancing its extension initiatives. By examining the inputs required for a sustainable extension program, this assessment provides valuable insights into the long-term viability and impact of the numeracy tutorial service. The research employs a mixed-methods approach that combines data analysis and qualitative analysis. The quantitative phase entails delivering pre- and post-tests to participants to assess their improvement in mathematics. In addition, the qualitative phase uses an evaluation form to collect feedback on the numeracy tutorial service to gather comprehensive data. The results reveal the strengths and weaknesses of the program, highlighting key areas for improvement. Furthermore, the data imply that Project KaISIPnayan creates a positive attitude toward mathematics and increases learners' confidence in mathematics. The findings emphasize the importance of program design, trained tutors, adequate resource allocation, and collaborative partnerships to ensure sustainability. The assessment contributes to the development of evidence-based strategies for enhancing numeracy tutorial services and provides valuable inputs for sustaining Project KaISIPnayan's extension initiatives. The findings of this study can guide organizations and educational institutions in designing effective and sustainable tutorial programs that promote numeracy skills among students, empowering them for lifelong success.